Curiosity in Learning Biology: Literature Review - Hunaepi Hunaepi; Muhammad Ikhsan; Hadi Suwono; Sulisetijono Sulisetijono (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
Previous research has shown that curiosity has an important role in education, especially in learning biological sciences. This review of literature study aims to examine the important role of curiosity in learning biological sciences. The focus in the study is 1) the nature of curiosity, 2) curiosity research in learning, and 3) curiosity in learning. The results of the study that curiosity has a positive contribution to learning include; 1) increase motivation and interest in learning, 2) develop critical thinking skills, creative thinking skills, and improve academic achievement. Curiosity can be developed and enhanced in learning by using problem Based Learning Models(PBL) , Project-Based Learning (PjBL), Inquiry, and Discovery Learning